Increasing Mobility of High Arctic Sea Ice Increases Marine Hazards Off the East Coast of Newfoundland. Issue 5 (15th March 2018) - Barber, D. G.; Babb, D. G.; Ehn, J. K.; Chan, W.; Matthes, L.; Dalman, L. A.; Campbell, Y.; Harasyn, M. L.; Firoozy, N.; Theriault, N.; Lukovich, J. V.; Zagon, T.; et al.
Abstract: Heavy ice conditions along Canada's east coast during spring 2017 presented hazardous conditions for the maritime industry and required the Canadian Coast Guard to pull its research icebreaker, CCGS Amundsen, off its scientific cruise to provide ice escort services and conduct search and rescue operations along Newfoundland's northeast coast. Greater ice concentrations and a thicker ice pack than are typical of this area created the anomalous ice cover. Within this paper we present in situ observations of the ice cover, confirming that pieces of multiyear sea ice from the high Arctic were present within the ice cover, and subsequently examine the transport pathway that connects the export of thick multiyear sea ice from the Lincoln Sea and Canadian Arctic Archipelago to coastal communities in Newfoundland. We conclude with a discussion on how an increasingly mobile Arctic sea ice cover may increase these ice hazards in the south. Plain Language Summary: Heavy ice conditions along Canada's east coast during spring 2017 presented hazardous conditions for the maritime industry at a time of year when vessels typically do not need to contend with sea ice. Greater ice concentrations and a thicker ice pack than are typical of this area created the anomalous ice cover. Our in situ observations from aboard the Canadian ice breaker Amundsen confirm that multiyear sea ice from the High Arctic was present and that two storms in late March compressed this thick ice cover onshore, where it persisted into late July. Within this work we connect the export of thick multiyear sea ice from the High Arctic and Canadian Arctic Archipelago to downstream areas where this thick multiyear ice cover is advected during winter. As the Arctic ice pack has declined in aerial extent and thickness, it has become increasingly mobile. This has contributed to increased ice transport through narrow channels along the periphery of the Arctic Ocean (i.e., Bering Strait, Nares Strait, and interisland straits of the Canadian Arctic Archipelago) and increased the presence of thick multiyear sea ice from the High Arctic at more southern locations that have typically not contended with such sea ice. Key Points: An anomalously thick and persistent ice pack along the east coast of Canada in spring 2017 created hazardous maritime conditions Within one sea ice season multiyear sea ice from the Lincoln Sea and Canadian Arctic was advected southward to the coast of Newfoundland An increasingly mobile Arctic ice pack is increasing ice flux through Nares Strait and releasing more ice hazards toward southern locations